Building The Potential of Permis and Rajik Villages as Ecotourism Villages in South Bangka Regency - Julia, Julia; Saputra, Darman (Institut Pariwisata Trisakti, 2021)
One of the villages that was developed as a tourist village is Permis Village and Rajik Village, South Bangka Regency, which are one of the villages that are members of the Fisheries, Plantation and Culture Cluster. Permis and Rajik Villages have development potential when viewed from a geographical and accessibility aspect. From a geographical aspect, Permis Village and Rajik Village are villages that are supported by the beach or the sea. From the aspect of accessibility, Permis Village and Rajik Village will be built a National Bridge connecting South Sumatra with Bangka. Based on this, this study aims to explore the potential for the development of Permis and Rajik Villages as local and cultural tourism villages based on studies of supply and demand aspects so that they are able to provide recommendations for future Village development. The approach used in this research is mixed methods, including qualitative methods to study supply aspects, community characteristics and policies, as well as quantitative methods to assess tourism demand aspects. The results showed that the Permis Village and the Rajik Village had the potential to be developed as local and cultural tourism villages. Keywords: Ecotourism, Community-Based Ecotourism, Permis Village, Rajik Village